2006
DOI: 10.1590/s1415-54192006000500012
|View full text |Cite
|
Sign up to set email alerts
|

Análise da confiabilidade e da correlação de dois índices de estimativa da maturação esquelética: índice carpal e índice vertebral

Abstract: OBJETIVO: o objetivo deste estudo foi avaliar a confiabilidade e a correlação de dois índices de estimativa da maturação esquelética. METODOLOGIA: foi utilizada uma amostra de 210 radiografias carpais e telerradiografias laterais, de arquivo, de pacientes de ambos os gêneros, com idade entre 7 e 18 anos. As radiografias carpais foram utilizadas na determinação do Índice de Maturação Carpal (IMC) e as telerradiografias laterais na determinação do Índice de Maturação Vertebral (IMV). Cada grupo de radiografias f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 5 publications
1
7
0
15
Order By: Relevance
“…In addition, works comparing CV assessments to the analysis of ossification events in the hand and wrist did not verify significant statistical differences for intra-and inter-examiner agreement levels (SANTOS et al, 2005;DAMIAN et al, 2006;JAQUEIRA et al, 2010;SACHAN et al, 2011). Jaqueira et al (2010) carried out a study comparing three different CV-based methods to assess skeletal maturation and showed that the method proposed by Bacetti et al (2002) is the most reliable and reproducible one.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, works comparing CV assessments to the analysis of ossification events in the hand and wrist did not verify significant statistical differences for intra-and inter-examiner agreement levels (SANTOS et al, 2005;DAMIAN et al, 2006;JAQUEIRA et al, 2010;SACHAN et al, 2011). Jaqueira et al (2010) carried out a study comparing three different CV-based methods to assess skeletal maturation and showed that the method proposed by Bacetti et al (2002) is the most reliable and reproducible one.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (DAMIAN et al, 2006;KAMAL et al, 2006;JOSHI et al, 2010;MAYARÍ and LUGO, 2010;WARMELING et al, 2010;MARTINS et al, 2011;ALTAN et al, 2012;MAHAJAN, 2012;MAYARÍ, 2012;PRASAD et al, 2013) have made estimates of skeletal growth potential by assessing CV radiographically and comparing the data obtained to that retrieved from hand-wrist films. While not all papers from our sample verified the reliability of methods that estimate skeletal maturation based on CV assessments, most authors agreed that different CV evaluation methods can deliver satisfactory and sufficiently reliable estimates of the degree of skeletal maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This intense growth is called pubertal growth spurge (PGS). This period is of the utmost importance in orthopedic orthodontic treatment, especially in cases of discrepancies of skeletal and dento-skeletal nature, because unlike dental disharmonies that can be solved at any time, if such divergences are not treated in this phase, the desired treatment results may not be achieved (4). PGS exhibits an increase in speed usually between 9 and 14 years of age.…”
Section: Introductionmentioning
confidence: 99%